2021
DOI: 10.1155/2021/8377362
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein, Baicalin, and Wogonin: Protective Effects against Ischemia‐Induced Neurodegeneration in the Brain and Retina

Abstract: Ischemia is a common pathological condition present in many neurodegenerative diseases, including ischemic stroke, retinal vascular occlusion, diabetic retinopathy, and glaucoma, threatening the sight and lives of millions of people globally. Ischemia can trigger excessive oxidative stress, inflammation, and vascular dysfunction, leading to the disruption of tissue homeostasis and, ultimately, cell death. Current therapies are very limited and have a narrow time window for effective treatment. Thus, there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 137 publications
0
24
0
Order By: Relevance
“…Proteomic studies were conducted to understand the regulatory mechanisms of baicalein against LPS-induced microglial activation. Previous reports showed that baicalein protects neurons against oxidative stress and lipid metabolism disorders ( 14 , 44 ). Consistently, our enriched GO and MPO analysis also demonstrated that baicalein mediates the biological processes of oxidation–reduction and lipid metabolic process ( Figures S1A, C ) .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Proteomic studies were conducted to understand the regulatory mechanisms of baicalein against LPS-induced microglial activation. Previous reports showed that baicalein protects neurons against oxidative stress and lipid metabolism disorders ( 14 , 44 ). Consistently, our enriched GO and MPO analysis also demonstrated that baicalein mediates the biological processes of oxidation–reduction and lipid metabolic process ( Figures S1A, C ) .…”
Section: Discussionmentioning
confidence: 96%
“…Baicalein (5,6,7-trihydroxyflavone; C 15 H 10 O 5 ; MW 270.2) is a major flavonoid extracted from the roots of the natural herb Scutellaria baicalensis Georgi (SB). SB is widely used in the clinic in Asia to treat various diseases and injuries, such as ischemic stroke and COVID-19 (13)(14)(15). Previous studies have shown that baicalein exerts a broad spectrum of bioactivity, including antioxidation, anti-apoptosis, and anti-excitotoxicity (16).…”
Section: Introductionmentioning
confidence: 99%
“…Scutellaria baicalensis Georgi, commonly known as Baikal skullcap or Chinese skullcap, is a widely used Chinese medicinal herb [106]. S. baicalensis extract and its three major active flavonoids, namely, baicalin, baicalein and wogonin showed low cytotoxicity and possessed neuroprotective, antioxidant, anti-inflammatory and anti-cancer properties [106][107][108].…”
Section: Scutellaria Baicalensis Georgi-baicalin Baicalein and Wogoninmentioning
confidence: 99%
“…Therefore, flavonoids have been evaluated for possible beneficial effects on a variety of acute and chronic human diseases. In vitro and in vivo studies have shown that flavonoids exert numerous benefits, such as anti-inflammatory [ 54 , 55 ], antioxidant [ 56 , 57 ], anticardiovascular [ 58 ], neuroprotective [ 59 , 60 ], and strong anticancer effects [ 61 , 62 , 63 ].…”
Section: Flavonoidsmentioning
confidence: 99%